Cardiovascular disease in patients with Type 2 diabetes mellitus: ambulatory therapeutist’s role in improving the quality of pharmaceutical prevention and treatment - E. A. Palferova (Российский кардиологический журнал)
As a part of a randomized clinical trial, the potential of patients’ education and monitoring by ambulatory therapeutists for improving pharmaceutical prevention and treatment effectiveness in Type 2 diabetes mellitus (DM-2) was evaluated. After 12 months, patients’ compliance and lipid level control improved significantly, as well as selfrated health and quality of life.